Implementation of Church Programs in Fostering the Integration of Christian Faith into Daily Living at Methodist Church in the Kaaga Synod, Kenya - Justus, Patrick Karani; Gichohi, Paul Maku; Kinoti, Mary (International Journal of Professional Practice, 2023)
The Church programs are meant to foster ethical and moral values in the society. However, there is a gap in implementation of church programs. This paper seeks to assess the implementation of church programs for fostering the integration of Christian faith into daily living within the Methodist Church in Kenya, Kaaga Synod. Men, women, and youth fellowships, missions’ teams, prayer groups, leadership and mentorship programs, and the children programs lack consistent implementation. If this problem remains unaddressed, it could lead to moral decadence, and render the Church irrelevant in the contemporary society. This study used a descriptive research design, qualitative approach, and proposes a constructivism research philosophy. The researcher establishes their analysis on transformational leadership theory, and leader-member exchange theory. The target population consisted 39,000 church members in 205 churches that make up the 27 circuits of Kaaga synod. The sample size was 380 respondents consisting of 339 church members, 32 lay leaders (including men, women, youth and circuit stewards), 8 superintendent ministers/clergy, and 1 synod Bishop. Data was collected using open-ended questionnaires for church members, interviews for lay leaders, focus group discussions for superintendent ministers, and documentary analysis for secondary data. The quality of data was ensured by checking content, construct, criterion, bracketing, and testimonial validities. Ethical clearance was obtained from the Kenya Methodist University, ethics committee and Nacosti. Data was analyzed thematically. Findings showed that Sunday school, youth and adult-member programs were present but lacked proper implementation and consistency necessary for fostering integration of Christian faith. This study recommended the Church leadership to support and oversee progressive implementation of church programs. It is also recommended that the Church leadership trains members on monitoring and evaluation of church structures. Adults were recommended to be role models to the young generation so as to enhance effective implementation of church programs.